A framework for multi-class-based multicast routing - Nicolau, Maria João (2002)
The goal of Differentiated Service Architecture is to provide the benefits of different CoS levels while avoiding the limitations of the IntServ model. This is accomplished by aggregating traffic into specific classes, thus changing the scope from QoS (per flow) to CoS (per class) guarantees. In presence of DiffServ networks, per flow path computation is not adequate. Instead, per class path calculation must be made and so multiple paths (unicast routing) or trees (multicast routing), must be computed in order to satisfy the different QoS requirements of different traffic classes. This paper presents a new multicast routing strategy enabling per class multicast tree computation. The proposed heuristics enable directed trees establishment, instead of reverse path ones, due to the importance of link asymmetry within an environment which is, essentially, unidirectional.